Transient Impact of Dysglycemia on Sputum Conversion among Smear-Positive Tuberculosis Patients in a Tertiary Care Facility in Ghana - Yorke, E.; Boima, V.; Dey, I.D.; Amissah-Arthur, M.; Ganu, V.; Amaning-Kwarteng, E.; Tetteh, J.; Mate-Kole, C.C. (SAGE, 2021)
BACKGROUND: Apart from increasing the risk of tuberculosis (TB), diabetes may be associated with more severe disease and lower rates of sputum conversion among TB patients. METHODS: We conducted a baseline cross-sectional study with a longitudinal follow-up of newly diagnosed smear-positive TB patients for 6 months. Sputum conversion rates between those with dysglycemia and those without were compared at 2 months (end of the intensive phase) and 6 months (end of the treatment). Descriptive statistics and logistic regression were computed to assess factors associated with dys glycemia as well as sputum conversion. RESULTS: A significantly higher proportion of normoglycemic patients had negative sputum compared with those with dysglycemia (83% vs 67%, P-value < .05) at 2 months but not at 6 months (87% vs 77%, P-value > .05). After controlling for age group and adjusting for other covariates, patients with dysglycemia were 66% less likely to convert sputum than those with normoglycemia. Females were at least 7 times more likely than males and those with high waist-to-hip ratio (WHR) of 88% were less likely compared with those with low WHR for sputum conversion at 2 months, respectively. At 6 months, females (compared with males) and those with high WHR (compared with those with normal WHR) were at over 9 times increased odds and 89% less likely for sputum conversion, respectively. CONCLUSION: A significantly lower proportion of smear-positive TB patients with dysglycemia converted to smear negative after 2 months of treatment but not at the end of the treatment, thus suggesting a transient impact of dysglycemia on sputum conversion.
Research Article
Keywords: Tuberculosis; smear Positive; dysglycemia; sputum Conversion; transient